Quando o carro da lei seca está por aqui, fica todo mundo receoso a beber e dirigir”: uma análise da efetividade da lei seca a partir do ponto de vista do destinatário da norma - Câmara, Cláudio Alysson Marinho (Universidade Federal Rural do Semi-Árido, 2018)
This work aimed to find elements that point out the conditions of effectiveness of the Prohibition Law during the trips during the vacation period to the beaches of Tibau / RN. It is a research with double orientation: theoretical and empirical. A literature study was carried out to analyze the forms of interaction of behavioral changes due to legislative changes, as well as highlighting the main innovations brought by Laws 11.705/08 and 12.760/12. Questionnaires were then applied to the target audience to assess the impact these changes brought to the daily lives of the people surveyed. The fieldwork was carried out in the city of Tibau/RN in summer houses, restaurants, tents and directly with the bathers that were in the beaches. The interviews were carried out on two weekends in January 2018. It is concluded that, in the space studied, the full effectiveness of the norm depends on the contribution of two factors: the presence of the inspection and the existence of alternative means for the displacement of the vacationers.
Artigo Acadêmico
Keywords: Efetividade; Lei Seca; Veraneio; Tibau/RN; Effectiveness; Prohibition Law; Summer; CIENCIAS SOCIAIS APLICADAS::DIREITO